Simulation of the response of microferrogel to external magnetic field - Ryzhkov, Aleksandr Vladimirovich; Raikher, Yurii Lvovich (Computational Continuum Mechanics, 2018)
A coarse-grained molecular dynamics method is used to investigate a microferrogel (MFG) that is a small polymer object containing nanoparticles of a magnetoactive filler. Although the applied magnetic field acts directly only on the particles, due to the coupling between these particles and the polymer, the structural and mechanical changes occur in the whole composite system. A study of these changes is important in view of widely discussed prospects of using MFG as field-controlled microcontainers for bioactive substances or drug delivery. In this work, a numerical model is proposed and realized, which enables one to perform a detailed analysis of stationary states of an MFG suspended in a neutral solvent. The effect of concentration of particles and their magnetic characteristics (magnetic moment magnitude, degree of uniaxial magnetic anisotropy, and interparticle dipolar coupling parameter) on structure formation in the absence of an external magnetic field and under its influence is investigated. It is shown that the chain-like aggregates are, in fact, the only type emerging in MFG. However, their effect on the polymer subsystem strongly depends on the type of magnetic anisotropy and on the concentration of the magnetic phase. This, in turn, entails different scenarios of the mechanical response of MFG and, in particular, the changes of the amount of solvent encased in the sample.